Multicentre randomized controlled trial comparing ferric(III)carboxymaltose infusion with oral iron supplementation in the treatment of preoperative anaemia in colorectal cancer patients. Issue 1 (December 2015) - Borstlap, W.; Buskens, C.; Tytgat, K.; Tuynman, J.; Consten, E.; Tolboom, R.; Heuff, G.; van Geloven, N.; van Wagensveld, B.; C.A. Wientjes, C.; Gerhards, M.; de Castro, S.; et al.
Abstract Background At least a third of patients with a colorectal carcinoma who are candidate for surgery, are anaemic preoperatively. Preoperative anaemia is associated with increased morbidity and mortality. In general practice, little attention is paid to these anaemic patients. Some will have oral iron prescribed others not. The waiting period prior to elective colorectal surgery could be used to optimize a patients' physiological status. The aim of this study is to determine the efficacy of preoperative intravenous iron supplementation in comparison with the standard preoperative oral supplementation in anaemic patients with colorectal cancer. Methods/Design In this multicentre randomized controlled trial, patients with an M0-staged colorectal carcinoma who are scheduled for curative resection and with a proven iron deficiency anaemia are eligible for inclusion. Main exclusion criteria are palliative surgery, metastatic disease, neoadjuvant chemoradiotherapy (5 × 5 Gy = no exclusion) and the use of Recombinant Human Erythropoietin within three months before inclusion or a blood transfusion within a month before inclusion. Primary endpoint is the percentage of patients that achieve normalisation of the haemoglobin level between the start of the treatment and the day of admission for surgery. This study is a superiority trial, hypothesizing a greater proportion of patients achieving the primary endpoint in favour of iron infusion compared to oral supplementation. A total of 198 patients will be randomized to either ferric(III)carboxymaltose infusion in the intervention arm or ferrofumarate in the control arm. This study will be performed in ten centres nationwide and one centre in Ireland. Discussion This is the first randomized controlled trial to determine the efficacy of preoperative iron supplementation in exclusively anaemic patients with a colorectal carcinoma. Our trial hypotheses a more profound haemoglobin increase with intravenous iron which may contribute to a superior optimisation of the patient's condition and possibly a decrease in postoperative morbidity. Trial registration ClincalTrials.gov:NCT02243735 .